The Concept of Ulum Al-Qur'an and Its Relevance in Contemporary Islamic Studies - Aulia, Clarissa Syahnaz; Suparman, Deden; Muchtar, Subhanallah; Sunandar, Dadan; Bashori, Abdul Hamid (Al Irsyad: Jurnal Studi Islam, 2025)
Ulum al-Qur'an is essential for understanding the Qur'an comprehensively, responding to contemporary challenges, and contextualizing its interpretation in light of historical, social, and technological developments. This research explores the Ulum al-Qur'an concept and its relevance in modern Islamic studies. A literature review method examines various primary and secondary sources related to Ulum al-Qur'an. The results show that Ulum al-Qur'an is a collection of sciences that discuss all aspects related to the Qur'an, such as revelation, compilation, recitation, exegesis (tafsir), tajwid, qira’at, abrogation (nasikh-mansukh), and textual criticism. Scholars such as Al-Qaththan, Al-Zarqani, and Ash-Shabuny emphasize the broad scope of these disciplines. In the contemporary context, Ulum al-Qur'an is essential for addressing modern challenges, preserving the text's authenticity, enhancing contextual understanding, and enriching academic Islamic studies. It also encourages a rational approach to interpreting the Qur’an and fosters constructive interfaith dialogue. Conclusion: Ulum al-Qur'an preserves the purity of Islamic teachings, addresses modern challenges, and bridges Islamic tradition with social context through rational and contextual approaches.